Moringa Leaf Extract Cream (Moringa oleifera L.)for Incision Wound Healing in White Rats - Dira, Asmarani; Puspitasari, Lia (Jurnal Ilmiah Kesehatan (JIKA), 2025)
The use of traditional medicinal plants is part of cultural heritage that holds great potential in supporting public health. Moringa leaves are known to accelerate the healing of incision wounds due to their bioactive compounds, including flavonoids, saponins, and terpenoids, which play a role in tissue recovery. This study aimed to evaluate the effectiveness of herbal cream containing Moringa leaf extract at concentrations of 2% w/w and 4% w/w in promoting the healing of incision wounds in white rats, assessed by wound closure length and histopathological examination of inflammatory cells. A true experimental design was applied in this research. The results showed that the Moringa leaf extract cream facilitated wound healing on the dorsal area of white rats within seven days and revealed a significant difference compared to the negative control group. Histopathological analysis demonstrated that treatment with 2% w/w and 4% w/w Moringa extract cream resulted in inflammatory cell counts of fewer than 50. In conclusion, herbal cream formulations containing 2% w/w and 4% w/w Moringa leaf extract are effective in healing incision wounds in white rats.